2020
DOI: 10.1108/jima-05-2019-0095
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the drivers of social media marketing in Malaysian Islamic banks

Abstract: Purpose This paper aims to attempt to investigate and test the factors related to social media advertisement that could forecast the intention to subscribe to Islamic banking products in Malaysia. Design/methodology/approach The research framework used in this study is guided by the Unified Theory of Acceptance and Use of Technology (UTAUT). The questionnaire method was used to collect data from 360 social media users and partial least square (PLS) analysis was carried out for the model’s validation. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 81 publications
2
29
0
2
Order By: Relevance
“…Moreover, Table 1 reported that there is one respondent who is more than 59 years old. This result is in line with a previous study conducted by Mohd Thas Thaker et al (2020), which stated that youngsters become potential customers in using Islamic bank's products because they actively engage in social media.…”
Section: Respondents' Demographicsupporting
confidence: 92%
“…Moreover, Table 1 reported that there is one respondent who is more than 59 years old. This result is in line with a previous study conducted by Mohd Thas Thaker et al (2020), which stated that youngsters become potential customers in using Islamic bank's products because they actively engage in social media.…”
Section: Respondents' Demographicsupporting
confidence: 92%
“…Past studies have verified that behavioral intention is a valid indicator for customers' intention to select Islamic credit cards (Ali, Raza & Puah, 2017). To use online Islamic banking services (Mansour, Eljelly & Abdullah, 2016), to Adopt/use Islamic banking (Ayyub et al, 2019;Charag, Fazili & Bashir, 2019;Hoque et al, 2019;Kaabachi & Obeid, 2016;Thaker et al, 2019b) to buy Islamic banking products and services (Hoque, Nik Hashim & Azmi, 2018;Maryam, Mehmood & Khaliq, 2019;Thaker et al, 2020a), and customer loyalty towards Islamic banking (Suhartanto et al, 2019b).…”
Section: Behavioural Intention Toward Islamic Banksmentioning
confidence: 99%
“…Scholars have focused on determinants of consumers' behavioural intention toward Islamic banking in varying degrees. For example, Thaker et al (2020a), in their survey on 360 social media users in Malaysia, found that perceived relevance, informativeness and perceived expectancy have a significant relationship with the behavioural intention of Islamic banking products via a social media platform. In another survey in Malaysia, Hoque et al (2019) used a sample of 273 respondents and found that customer-bank relationships are essential determinants of customers' behavioural intention in Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations